Adverse outcome pathways associated with the ingestion of titanium dioxide nanoparticles : a systematic review - Rolo, Dora; Assunção, Ricardo; Ventura, Célia; Alvito, Paula; Gonçalves, Lídia; Martins, Carla; Bettencourt, Ana; Jordan, Peter; Vital, Nádia; Pereira, Joana; Pinto, Fátima; Matos, Paulo; et al. (MDPI, 2022)
Titanium dioxide nanoparticles (TiO2-NPs) are widely used, and humans are exposed through food (E171), cosmetics (e.g., toothpaste), and pharmaceuticals. The oral and gastrointestinal (GIT) tract are the first contact sites, but it may be systemically distributed. However, a robust adverse outcome pathway (AOP) has not been developed upon GIT exposure to TiO2-NPs. The aim of this review was to provide an integrative analysis of the published data on cellular and molecular mechanisms triggered after the ingestion of TiO2-NPs, proposing plausible AOPs that may drive policy decisions. A systematic review according to Prisma Methodology was performed in three databases of peer-reviewed literature: Pubmed, Scopus, and Web of Science. A total of 787 records were identified, screened in title/abstract, being 185 used for data extraction. The main endpoints identified were oxidative stress, cytotoxicity/apoptosis/cell death, inflammation, cellular and systemic uptake, genotoxicity, and carcinogenicity. From the results, AOPs were proposed where colorectal cancer, liver injury, reproductive toxicity, cardiac and kidney damage, as well as hematological effects stand out as possible adverse outcomes. The recent transgenerational studies also point to concerns with regard to population effects. Overall, the findings further support a limitation of the use of TiO2-NPs in food, announced by the European Food Safety Authority (EFSA).
Keywords: titanium dioxide nanoparticles; human exposure; ingested TIO2-NPs; AOP; nanosafety; colorectal cancer; adverse outcomes